TINJAUAN SYARIAH TENTANG PENERAPAN AKAD IJARAH AL MUNTAHIYAH BI AL-TAMLIK DI PERUSAHAAN LEASING SYARIAH - Mudzakkir, Muhammad Fakhruddin; Graha, Andi Nu (UIN Sayyid Ali Rahmatullah Tulungagung, 2015)
Public need for their fnancing of capital goods in accordance with the principles of Islam, encourages businesses and governments to create the Islamic fnance company. Basic application of sharia leasing transactions between customers through Ijarah Al Muntahiyah bi Al Tamlik contract based on the Fatwa Dewan Syariah Nasional No. 09/DSN-MUI/IV/2000 about ijarah fnancing and Fatwa Dewan Syariah Nasional No. 27/DSN-MUI/III/2002 about Ijarah Al Muntahiyah bi Al Tamlik fnancing. Implementation of sharia fnance leasing company to its customers are still not in accordance with the provisions of DSN 27/DSN-MUI/III/2002 and hadith.Keywords : leasing fnance, ijarah al muntahiyah bi al tamlik